Czy pacjenci po przeszczepie nerki są świadomi konieczności stosowania ochrony przeciwsłonecznej? - Anna Wojas-Pelc; Władysław Sułowicz; Joanna Sułowicz (Termedia Publishing House, 2011)
Introduction. Organ transplant recipients are at 10-fold higher risk ofdeveloping basal cell carcinoma and up to 250-fold higher risk of developingsquamous cell carcinoma compared with the general population.Common risk factors include the type of immunosuppression, fair skin,male gender, older age and sunlight.Objective. To evaluate patients' compliance with sunlight protectionbefore and after renal transplantation.Material and methods. The study covered 455 patients after renal transplantationaged 18-74 years. A special questionnaire was used to determineage, gender, place of residence, skin type (according to the Fitzpatrickclassification), hair and eye colour, and any episodes of sunburn.Outdoor occupation, frequency of sun exposure and residence in a hotclimate for a long time were taken into consideration for evaluation ofUV exposure. Information about use of sunscreens and protectiveclothes before and after the renal transplant procedure were also noted.Results. Before the renal transplant procedure only 20% of patientsavoided sun at midday (11 am - 4 pm) compared to 64% of patientsafter renal transplantation. Sunscreens were used by 15.4% vs. 20% andprotective clothes 7.7% vs. 21.8% of patients respectively. After therenal transplant procedure 57.6% of patients started to use at least oneof the methods of skin cancer prophylaxis. After transplantation 44% ofpatients (p < 0.01) reported limiting time spent outdoors. 17.1% ofpatients started to use or used more frequently protective clothes(p < 0.0022) and 14.1% sunscreen creams (p < 0.0315) compared to thesituation before the surgical procedure. No sun protection such as protectiveclothes or sunscreen creams was still used by 78.2% and 80% ofpatients, respectively.Conclusions. There is insufficient protection against UV light amongpatients after renal transplantation, so further education is needed.